Who Rules the World? Reframings - Noam, Chomsky (New York Macmillan Audio, 2016)
Noam Chomsky is the world's foremost intellectual activist. Over the last half century, no one has done more to question the great global powers who govern our lives, forensically scrutinizing policies and actions, calling our politicians, institutions and media to account.
Keywords: Globalisation